2007
DOI: 10.1007/s00414-007-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of experimental cranial skin wounding from screwdriver trauma

Abstract: As part of a more extensive investigation of skin wounding mechanisms, we studied wounds created by five common screwdrivers (straight, star, square or Robertson, Posidriv and Phillips) on the shaven foreheads of 12 freshly slaughtered pigs. We fixed the different screwdriver heads to a 5-kg metal cylinder which was directed vertically onto each pig head by a droptube of 700 mm length. We examined skin lesions by photography and also by scanning electron microscopy (SEM). Our evaluation of differences in wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In practice, this will affect the ability to distinguish the subtle differences between non-serrated and serrated blades. The surface of a blade can also result in striations on the kerf wall that can be related to saw or knife class [14,24] although one would also expect this to be affected by the ratio of cancellous to compact bone at the cutmark site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In practice, this will affect the ability to distinguish the subtle differences between non-serrated and serrated blades. The surface of a blade can also result in striations on the kerf wall that can be related to saw or knife class [14,24] although one would also expect this to be affected by the ratio of cancellous to compact bone at the cutmark site.…”
Section: Discussionmentioning
confidence: 99%
“…As such, this technique is non-destructive and arguably more precise than traditional methods. Furthermore, it has been used in previous research of this nature [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings showed that there was a direct correlation between the penetration mechanism and the geometry of the punch tip [20]. Kieser et al showed that a sharp tip punch penetrated via a mode I crack whereas a blunt tip exhibited a mode II crack [21,22].…”
Section: Synthetic Skin Simulantsmentioning
confidence: 95%